The Research of Hydraulic Cylinder Controlled by Digital Valve - Zhi-hao Liu; Qin-he Gao; Jing-yue Li; Hai-long Niu (Institute of Advanced Engineering and Science, 2014)
This paper aims to research the position control of the hydraulic cylinder controlled by the high-speed on-off valve to realize the precise position control. A compound algorithm of proportional integral & speed feedforward- displacement feedback is put forward based on the research on the relationship between the duty ratio and the past flow for the high speed on-off valve. The speed feedforward-displacement feedback algorithm can solve the hysteresis resulting from the feedback control and be considered as the certain duty ratio is given ahead, and the proportional integral control algorithm is designed and utilized to deal with the position error by adjusting to the duty ratio of high speed on-off valve. The genetic algorithm is used to tune the control parameters, including speed forward coefficient, proportional and integral coefficient of displacement feedback, output coefficient to gain the optimization result, on terms of the performance of the position control system. The mathematics modeling is analyzed and simulated with Simulink using the bulk-cavity-node method, and the hydraulic loop is established to verify the simulation result with the optimized results on the FESTO platform. the research finds that the proposed position scheme is effective to increase the position precision, and the position control parameters optimized by genetic algorithm can decrease the position error more. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4218